Pengenalan Bahasa Inggris Pada Anak Usia Dini Melalui Media Flash Card Di TK Tunas Karya Kemlagi Kabupaten Mojokerto - Sonya Brinda; Risma Rahajeng Lestari; Irham Miftakhul Jannah; Sherly Citra Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This journal examines The development of english learning strategies by using flash card for early childhood in Tunas Karya kindergarten, Mojodadi Village, Kemlagi District, Mojokerto. The research aims to analyze the english learning in kindergarten.. The research is using the classroom action research to improve the learning practice in the classroom, so that the learning practice can be done in more professional way. The results indicate that some factors, such as changes, can be happened in english childhood vocabulary.